Bacterial endophytes diversity of tree legumes from Argentina - Martínez Alcántara, Virginia (2020)
The aim of this work was to isolate and characterize, based on microbiological as well as molecular markers, bacteria within nodules of three native trees species from South America: Poecilanthe parviflora Benth (Lapachillo), Vachellia caven (Molina) Seigler & Ebinger (Espinillo), and Enterolobium contortisiliquum (‎Vell.‎) ‎Morong (Timbo). In line with this, we isolated and characterized 15 bacteria from P. parviflora, 6 from V. caven and 1 from E. contortisiliquum. Among them we identified representatives of Bradyrhizobium sp. from E. contorsiliquum and P. parviflora, as well as of Ensifer sp. (Sinorhizobium) and Mesorhizobium sp. from V. caven. Also, other bacteria were found, like representatives of Bacillus sp., Microbacterium sp. and Curtobacterim sp., as well as Caulobacter sp., Dyella sp., Pseudomonas sp. and Enterobacter sp. Some of these isolates inhibited the growth of two fungal plant pathogens. So, nodules of these native legumes not only are occupied by highly diverse rhizobia but also by other bacteria that might promote plant growth.